Phenotyping cardiogenic shock that showed different clinical outcomes and responses to vasopressor use: a latent profile analysis from MIMIC-IV database - Yu, Yue; Rao, Jin; Xu, Qiumeng; Xiao, Jian; Cheng, Pengchao; Wang, Junnan; Xi, Wang; Wang, Pei; Zhang, Yufeng; Wang, Zhinong (Frontiers in Medicine, 2023)
Background: Cardiogenic shock (CS) is increasingly recognized as heterogeneous in its severity and response to therapies. This study aimed to identify CS phenotypes and their responses to the use of vasopressors. Method: The current study included patients with CS complicating acute myocardial infarction (AMI) at the time of admission from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Laboratory and clinical variables were collected and used to conduct latent profile (LPA) analysis. Furthermore, we used a multivariable logistic regression (LR) model to explore the independent association between the use of vasopressors and endpoints. Result: A total of 630 eligible patients with CS after AMI were enrolled in the study. The LPA identified three profiles of CS: profile 1 (n=259, 37.5%) was considered as the baseline group; profile 2 (n=261, 37.8%) was characterized by advanced age, more comorbidities, and worse renal function; and profile 3 (n=170, 24.6%) was characterized by systemic inflammatory response syndrome (SIRS)-related indexes and acid-base balance disturbance. Profile 3 showed the highest all-cause in-hospital mortality rate (45.9%), followed by profile 2 (43.3%), and profile 1 (16.6%). The LR analyses showed that the phenotype of CS was an independent prognostic factor for outcomes, and profiles 2 and 3 were significantly associated with a higher risk of in-hospital mortality (profile 2: odds ratio [OR] 3.95, 95% confidence interval [CI] 2.61-5.97, P<0.001; profile 3: OR 3.90, 95％CI 2.48-6.13, P<0.001) compared with profile 1. Vasopressor use was associated with an improved risk of in-hospital mortality for profile 2 (OR: 2.03, 95% CI: 1.15-3.60, P=0.015) and profile 3 (OR: 2.91, 95% CI: 1.02-8.32, P=0.047), respectively. The results of vasopressor use showed no significance for profile 1. Conclusion: Three phenotypes of CS were identified, which showed different outcomes and responses to vasopressor use.